Skogsskötselplanens betydelse - Ollas, Marcus (2016)
How meaningful is a forest management plan, is it something that every forest owners must have for their property, or is it enough that they have a plan in their head? This study is conducted is to find out how meaningful a forest management plan is for Mellanskog members in Vo Northern Dalarna. We have chosen in this case to get answers through a questionnaire survey. The questionnaire contains questions that are both open and closed. The questionnaires together with an explaining letter were sent to 69 members who were chosen at random through Mellanskogs own members list. The result from the study shows that most forest owners plan correct measures with the help of the plan and therefore one can assume that it will be used. The forest owners prefer to read the plan from the file and the forest owners received a personal review with an inspector. The forest owners did not think that the forest management plan was difficult to understand. They thought that it was enough with a new forest management plan every 10 years. Most forest owners think that it is an inferior care if they not have a current forest management plan. It shows that forest owners realize what can happen if you not have a current. There is a very high percentage who think that the forest management plan is important.